Adjuvant Chemoradiotherapy for Gastric Cancer: Efficacy and Cost-Effectiveness Analysis - Zhang, Mengxi; Wen, Feng; He, Xiaofeng; Zhang, Weihan; Hu, Jiankun; Li, Qiu (Frontiers in Oncology, 2019)
Purpose: The benefit of adjuvant chemotherapy (CT) for localized gastric cancer (GC) after D2-gastrectomy has been clearly demonstrated. However, adjuvant chemoradiotherapy (CRT) remains controversial. This study aimed to assess the efficacy and cost-effectiveness of treatment for GC after D2-gastrectomy. Materials and methods:Stage IB-IIICGC patients who had received adjuvant CRT or CT, or who had just been observed after D2-gastrectomy were retrospectively selected. Therapeutic strategy after surgery, disease-free survival (DFS), overall survival (OS), adverse events and costs were recorded retrospectively. A Markov model was developed to simulate the process of GC after D2-gastrectomy.Health outcomes were measured using quality-adjusted life-years (QALYs). Incremental costeffectiveness ratio (ICER) was regarded as the primary outcome. Results: A total of 254 patients were selected. Three year OS and DFS were 83.02% and 64.15% in the adjuvant CRT group, 74.19% and 63.54% in the adjuvant CT group, and 45.45% and 43.35% in the observation group. Total grade 3 or 4 toxicity was higher in the CRT group than in the CT group (54.72% versus 37.10%, p < 0.05). The ICER of the CT and CRT groups versus the observation group were $10,571.55 and $11,467.41 /QALY, respectively. The probability of CT, CRT and observation being cost-effective were 28.9%, 37.9% and 33.2%, respectively, when a willingness-to-pay threshold (WTP) of $25,648.45/QALY was used. Conclusions: Adjuvant CRT was associated with improved OS and DFS compared with adjuvant CT and postoperative observation. Both adjuvant CRT and CT are likely to be cost effective compared with postoperative observation. However, adjuvant CRT was the optimal choice for a WTP threshold of $25,648.45/QALY.